Development of an Ecosystem Module Based on Papuan Local Wisdom Using the ADDIE Model to Enhance Students’ Higher Order Thinking Skills (HOTS) - Muhamad Imron; Dwi Yarmalinda; Yenniwati Sinaga; Roy Marthen Rahanra (Yayasan Darussalam Bengkulu, 2026)
This study aims to develop an ecosystem module based on Papuan local wisdom using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) and to examine its validity, practicality, and effectiveness in improving students’ Higher Order Thinking Skills (HOTS). This research employs a Research and Development (R&D) approach with an effectiveness test design using a one-group pretest–posttest design. The subjects of this study were students of the Biology Education Study Program at STKIP PGRI Papua. The module development process was carried out through the five stages of the ADDIE model, including needs analysis, design, product development, implementation, and evaluation. The research instruments consisted of expert validation sheets, practicality questionnaires, and HOTS-based essay tests. Data were analyzed using descriptive quantitative techniques, N-gain analysis, paired t-test, and effect size calculation. The results showed that the developed module had a very high level of validity with an average score of 3.69 and a very high level of practicality with a percentage of 89%. The effectiveness test indicated a significant improvement in students’ HOTS, with an N-gain score of 0.61 (moderate category), a t-test significance value of p < 0.05, and an effect size of 1.25 (large category). These findings indicate that the ecosystem module based on Papuan local wisdom is effective in enhancing students’ abilities in analysis, evaluation, and creation. Therefore, the developed module is considered valid, practical, and effective, and can be used as an innovative teaching material in contextual biology learning based on local wisdom.